2009
DOI: 10.1002/dvdy.21699
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic function of FGF‐4: Its role in development and stem cells

Abstract: Fibroblast growth factors (FGFs) were initially recognized as fibroblast-specific growth factor, and it is now apparent that these growth factors regulate multiple biological functions. The diversity of FGFs function is paralleled by the emerging diversity of interactions between FGF ligands and their receptors. FGF-4 is a member of the FGF superfamily and is a mitogen exhibiting strong action on numerous different cell types. It plays a role in various stages of development and morphogenesis, as well as in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 132 publications
(144 reference statements)
4
29
1
Order By: Relevance
“…This may suggest that FGF4 may not be regulated through the Oct4-Sox2 complex but by another system or pathways that caused the upregulation of FGF4 at P20 of ASCs. In addition, FGF4 may also be a cancer marker as it was found to be upregulated in breast cancer via Oct3 activation [29,30]. However, in this study, we believe that the increase in FGF4 expression is due to the feedback mechanism of maintaining the self-renewal ability of ASCs at later passage when the growth kinetics of ASCs was slowing down.…”
Section: Discussioncontrasting
confidence: 67%
“…This may suggest that FGF4 may not be regulated through the Oct4-Sox2 complex but by another system or pathways that caused the upregulation of FGF4 at P20 of ASCs. In addition, FGF4 may also be a cancer marker as it was found to be upregulated in breast cancer via Oct3 activation [29,30]. However, in this study, we believe that the increase in FGF4 expression is due to the feedback mechanism of maintaining the self-renewal ability of ASCs at later passage when the growth kinetics of ASCs was slowing down.…”
Section: Discussioncontrasting
confidence: 67%
“…In response to CaSR stimulation, MDA-MB-231 breast cancer cells secrete GM-CSF, EGF, MDC, FGF-4 and IGFBP-2 via a mechanism that requires transactivation of EGFR and involves ERK, PI3K-AKT-mTOR and PKC signaling pathways. The identified cytokines and growth factors most likely exert an integrated effect on endothelial cells, as independent reports focusing on individual cytokines and growth factors have demonstrated their angiogenic potential [78][79][80][81][82][83][84][85][86]. Thus, our results suggest that the joint potential of multiple chemotactic and angiogenic mediators secreted in response to CaSR activation putatively contributes to the aggressiveness of breast cancer cells.…”
Section: Discussionmentioning
confidence: 67%
“…This factor is an autocrine and/or paracrine growth factor required for multiple cellular events during embryogenesis [6]. It was previously found that FGF4 increases proliferation of neural progenitors [7] or bone marrow mesenchymal stem cells (BMMSCs) [8] and sustains the survival of trophoblast stem cells [9].…”
Section: Introductionmentioning
confidence: 99%